2018
DOI: 10.1186/s12931-018-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in patients with cirrhosis: risk factors associated with mortality and predictive value of prognostic models

Abstract: BackgroundCirrhosis always goes with profound immunity compromise, and makes those patients easily be the target of pneumonia. Cirrhotic patients with pneumonia have a dramatically increased mortality. To recognize the risk factors of mortality and to optimize stratification are critical for improving survival rate.MethodsTwo hundred and three cirrhotic patients with pneumonia at a tertiary care hospital were included in this retrospective study. Demographical, clinical and laboratory parameters, severity mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
(38 reference statements)
0
14
0
3
Order By: Relevance
“…Ebenso kann sich eine chronische Leberinsuffizienz verschlechtern [8,190]. Deshalb sollten bei Aufnahme im Labor die Transaminasen und Cholestaseparameter bestimmt werden.…”
Section: Monitoring Der Organfunktionunclassified
“…Ebenso kann sich eine chronische Leberinsuffizienz verschlechtern [8,190]. Deshalb sollten bei Aufnahme im Labor die Transaminasen und Cholestaseparameter bestimmt werden.…”
Section: Monitoring Der Organfunktionunclassified
“…Pneumonia is one of the most common infections in liver disease patients with cirrhosis admitted in CCU. [1,2] The prevalence of pneumonia is reported in about 21.4% of cirrhotic patients with mortality rates as high as 37%-41%. [3] There are several consequences of pneumonia in cirrhotic patients which include acute on chronic liver failure, multiple organ failure, sepsis, prolonged hospitalization, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic liver diseases are at high risk of contracting infections, due to increased bacterial translocation and immune suppression associated with decreased liver function [ 35 ]. For instance, pneumonia is a common infectious disease in cirrhotic patients [ 36 , 37 ]. In the current study, cirrhotic patients showed significantly higher morbidity of postoperative pulmonary infection compared with patients in the control group.…”
Section: Discussionmentioning
confidence: 99%